2013
DOI: 10.1186/2228-5547-4-31
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of multicore phenol formaldehyde microcapsules and their application in polyurethane paint formulation for self-healing anticorrosive coating

Abstract: Homo-and copolymers of 2-(N-phthalimido)ethyl methacrylate (NPEMA) and p-chlorophenyl methacrylate (PCPMA) were prepared in N,N-dimethyl formamide (DMF) solution at 70 °C using 2,2-azo-bisisobutyronitrile (AIBN) as initiator. The nano-CdS-doped polymer composite of NPEMA and PCPMA was prepared via in situ technique. The homo-and copolymers of NPEMA and PCPMA were characterized using FT-IR spectroscopy and gel permeation chromatography (GPC). The polymer nano composites were characterized using FT-IR spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 20 publications
1
21
0
1
Order By: Relevance
“…Li et al [22] investigated mechanical performance and self-healing achieved by the induction of microwaves in thermoplastic polyurethane composites reinforced by Graphene-CNT. Jadhav et al [23] created microcapsules with phenol-formaldehyde resin shells and kernels containing drying and corrosion resistant agents and linseed oil. They observed that the roughness and toughness of the shell surface to provide better compatibility with the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [22] investigated mechanical performance and self-healing achieved by the induction of microwaves in thermoplastic polyurethane composites reinforced by Graphene-CNT. Jadhav et al [23] created microcapsules with phenol-formaldehyde resin shells and kernels containing drying and corrosion resistant agents and linseed oil. They observed that the roughness and toughness of the shell surface to provide better compatibility with the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works offer effective self-healing systems with linseed oil as healing agent 7,8 . Jadhav et al 7 created microcapsules with shell made from phenol-formaldehyde resin and core containing drier and corrosion inhibitor along the mentioned above oil.…”
Section: Microcontainersmentioning
confidence: 99%
“…Jadhav et al 7 created microcapsules with shell made from phenol-formaldehyde resin and core containing drier and corrosion inhibitor along the mentioned above oil. They noticed that roughness or toughness of shell surface provides better compatibility with polymer matrix 7 . Tatiya et al created polyurea microcapsules made from polyamidoamine dendrimer of zero generation.…”
Section: Microcontainersmentioning
confidence: 99%
“…Most of them are based on existing concepts in different coatings obtained with other techniques. Self-healing materials have been largely investigated for restoring the initial barrier properties of the coating, hence protecting the metallic surface against corrosion (Jadhav et al, 2013). The presence of dyes in the coating that can be released when the coating is damaged reveals visually those impacted areas and thus makes them accessible to repair processes leading to reduced maintenance costs and longer life span of the components.…”
Section: Types Of Functionalization and Potential Applicationsmentioning
confidence: 99%